Effect of E-Service Quality on E-Satisfaction and E-Loyalty: Moderated by Purchase Frequency - Ngatno; Eka Ariyanti, Azwina (Archives of Business Research, 2021)
This study aims to analyze the effect of e-service quality on e-satisfaction and e-loyalty by moderating purchase frequency. Data were collected from respondents, namely GrabFood customers in Batam City. The data were analyzed using the multi-group model with AMOS 23. The results showed that e-service quality had a positive effect on e-satisfaction. Besides, e-satisfaction also has a positive effect on e-loyalty. Meanwhile, the multi-group test shows that the frequency of purchases strengthens the relationship between e-service quality and e-satisfaction. On the other hand, purchase frequency is not able to moderate the relationship between e-satisfaction and e-loyalty. It is recommended for further research to study how the impact of this GrabFood can increase sales from its customers.